The effect of nitric oxide combined with fluoroquinolones against Salmonella enterica serovar Typhimurium in vitro - Coban,AY (2003)
Two regulons, soxRS and marRAB, are associated with resistance to quinolones or multiple antibiotic in Salmonella enterica serovar Typhimurium. These regulons are activated by nitric oxide and redox-cycling drugs, such as paraquat and cause on activation of the acrAB-encoded efflux pump. In this study, we investigated the effect of nitric oxide (NO) alone and in combination with ofloxacin, ciprofloxacin, and pefloxacin against S. typhimurium clinical isolates and mutant strains in vitro. We did not observe synergistic effect against clinical isolates and SH5014 (parent strain of acr mutant), while we found synergistic effect against PP120 (soxRS mutant) and SH7616 (an acr mutant) S. typhimurium for all quinolones. Our results suggest that the efficiencies of some antibiotics, including ofloxacin, ciprofloxacin, and pefloxacin are decreased via activation of soxRS and marRAB regulons by NO in S. enterica serovar Typhimurium. Further studies are warranted to establish the interaction of NO with the genes of Salmonella and, with multiple antibiotic resistance.